Broadening the understanding of the reality of the drug addict subject - Silvestre, Karollyni Maia Pinheiro; Barcellos, Laura Rangel Oliveira; Ribeiro , Maria Luiza Soares Motta; Ribeiro-Andrade, Érica Henrique (Seven Editora, 2023)
In many communities it has become a habit that facilitates communication, insertion into groups and makes the user feel belonging to the community. The user is not able to administer the use of them and often feels ineffective and incompetent. Therefore, there is an important role in the process of improving addictions and social bonds, as well as improving the self-esteem of treatment-related issues. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-105